Isopropyl derivative of cyclofructan 6 as chiral selector in liquid chromatography and capillary electrophoresis - Maier, Vítězslav; Kalíková, Květa; Přibylka, Adam; Vozka, Jiří; Smuts, Jonathan; Svidrnoch, Martin; Sevčík, Juraj; Armstrong, Daniel W; Tesařová, Eva (Journal of chromatography. A, 2014)
Cyclofructans and preferentially their derivatives can serve as chiral selectors for the separation of different enantiomers/atropisomers. Moreover, the strong ionophoric nature of the 18-crown-6 ether core of cyclofructan 6 for barium cations may be exploited to enhance or modify enantioselectivity. In this work isopropyl-cyclofructan-6 was used as a chiral selector for the separation of binaphthyl atropisomers in HPLC and CE. The data from both separation systems were compared with each other. While in HPLC the chiral selector was bonded to silica gel to afford a chiral stationary phase, in capillary electrophoresis it was freely mobile in the background electrolytes (BGE). This significant difference is reflected in the separation potential of the two separation systems. All five analytes could be baseline separated in HPLC (reversed phase mode) while only one derivative was baseline resolved in CE. This result was attributed to the more rigid nature of the immobilized chiral selector. Addition of Ba(2+) to the mobile phase or BGE improved chiral separations in both systems. The results may help to elucidate the interaction mechanism in these systems with cyclofructan derivatives and to gain some general knowledge of their separation potential.
Keywords: vysokoúčinná kapalinová chromatografie; Electrolytes; Atropisomer; Capillary electrophoresis; Isopropyl-cyclocfructan-6; elektrolyty; Chiral separation; Chromatography, High Pressure Liquid; Cyclofructan; High performance liquid chromatography; Electrophoresis, Capillary; Fructans; chromatografie s reverzní fází; Chromatography, Reverse-Phase; Stereoisomerism; stereoizomerie; elektroforéza kapilární; fruktany